1996
DOI: 10.1002/(sici)1097-0231(199608)10:11<1327::aid-rcm560>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Odors Emitted by Freshly CutAllium Using Combined High-performance Liquid Chromatography and Mass Spectrometry

Abstract: Allium odors were re-examined to determine whether or not they contain degradation compounds of thiosulfinates. Garlic (Allium sativum), leek (Allium porrum) and onion (Allium cepa) were investigated using cryotrapping and direct injection of aqueous solutions of the samples into a high-performance liquid chromatograph (HPLC), with a diode-array detector, coupled to a maw spectrometer (MS). Various commercial systems which couple HPLC to tandem MS, but using different ionization systems, were compared. Best re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 1 publication
(1 reference statement)
1
16
0
1
Order By: Relevance
“…In order to confirm the identity of the isolated allicin, the major antibacterial compound in garlic, the extracts were then analyzed by LC-MS and then had been isolated by preparative HPLC. The electrospray mass spectral fragmentation of allicin was found to be similar with published values (Calvey et al, 1994;Ferary et al,1996). γ -Glutamyl-Sallylcysteine was also identified from its (M+H) + ion and the MS 2 fragmentation pattern thereafter.…”
Section: Lc-ms Analysis Of Garlic Extractmentioning
confidence: 99%
“…In order to confirm the identity of the isolated allicin, the major antibacterial compound in garlic, the extracts were then analyzed by LC-MS and then had been isolated by preparative HPLC. The electrospray mass spectral fragmentation of allicin was found to be similar with published values (Calvey et al, 1994;Ferary et al,1996). γ -Glutamyl-Sallylcysteine was also identified from its (M+H) + ion and the MS 2 fragmentation pattern thereafter.…”
Section: Lc-ms Analysis Of Garlic Extractmentioning
confidence: 99%
“…10,11 Now HPLC/UV and HPLC/ MS methods are generally applied for the analysis of constituents of garlic with suitable sampling methods. [12][13][14] However, as far as we know, direct analysis of crude garlic has not been reported previously.…”
mentioning
confidence: 92%
“…Steam distillation (SD), solvent extraction, and supercritical fluid extraction (SFE) have usually been employed for isolation and extraction of garlic flavors [2,10,11,14,15]. Recently, active studies on Allium flavors were reported by Auger and Ferary and their co-workers; they employed several different isolation methods such as extraction, trapping on Tenax, cold trapping, headspace solid-phase microextraction (HS-SPME) and hyphenated chromatographic procedures [12,13,14,19,20,21]. According to their reports, Allium odors contain only thiopropanal S-oxide and thiosulfinates as sulfur volatiles [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, active studies on Allium flavors were reported by Auger and Ferary and their co-workers; they employed several different isolation methods such as extraction, trapping on Tenax, cold trapping, headspace solid-phase microextraction (HS-SPME) and hyphenated chromatographic procedures [12,13,14,19,20,21]. According to their reports, Allium odors contain only thiopropanal S-oxide and thiosulfinates as sulfur volatiles [21]. In addition, they claimed that gas chromatography-mass spectrometry (GC-MS) did not seem to be a suitable method for the analysis of true garlic flavor as it gave many artifacts [12,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation